Intraluminal Administration of Resiniferatoxin Protects against Clostridium difficile Toxin A-Induced Colitis. (18th April 2017) - Vigna, Steven R.
Abstract : Clostridium difficile toxin A is a colonic inflammatory agent that acts partially by activation of TRPV1 (transient receptor potential vanilloid type 1). Resiniferatoxin (RTX) is an excitotoxin that activates TRPV1 at low concentrations and defunctionalizes TRPV1 at high concentrations. RTX at various doses was injected intraluminally into isolated ileal segments in anesthetized rats. After 3 hours, the treated segments were removed and inflammation was assessed. This acute treatment with RTX resulted in biphasic responses: (1) an increase in inflammation similar to that caused by toxin A and capsaicin at low doses of up to 100 ng RTX and (2) no inflammatory effect of RTX at higher doses (1–100  μ g), consistent with a defunctionalizing or neurotoxic effect of RTX at high doses. Separately, anesthetized rats were treated with RTX enemas and one or four weeks later were challenged with toxin A. Toxin A-induced colitis was significantly inhibited one week after an RTX enema, and this effect was RTX dose dependent. When tested four weeks after administration of the RTX enema, protection against toxin A colitis was lost. In conclusion, an RTX enema protects against toxin A-induced colitis in rats for at least one week but less than four weeks.